PENGARUH KOMBINASI PUPUK KANDANG DAN PUPUK MAJEMUK SERTA DOSIS ARANG SEKAM PADA PERTUMBUHAN DAN PRODUKSI CABAI RAWIT HIBRIDA (Capsicum annum L.) - Widya Aliv Pakerti; D.W. Widjajanto; Eny Fuskhah (Jurnal Agrotech, 2021)
The experiment was aimed to determine the effect of combination dosage organic fertilizer with compound fertilizer and dosage husk charcoal, also the interaction both of treatment on the growth and production of hybrid cayenne pepper. A completely randomized factorial design (4x6) with 3 replications was used throughout the experiment. The first factor was dosage husk charcoal (A) namely A0 = control, A1 = 40 g husk charcoal/8 kg soil, A2 = 80 g husk charcoal/8 kg soil, A3 = 120 g husk charcoal/8 kg soil. The second factor was combination dosage of organic fertilizer and compound fertilizer (B) namely B0 = control, B1 = 100% organic fertilizer, B2 = 75% organic fertilizer + 25% compound fertilizer, B3 = 50% organic fertilizer + 50% compound fertilizer, B4 = 25% organic fertilizer + 75% compound fertilizer dan B5 = 100% compound fertilizer. Parameters observed were plant height, total number of fruits per plant, total weight of fruits per plant, fresh weight per plant, harvest index. Collected data were analyzed using ANOVA and Duncan Test was employed for further analysis. Experiment showed that application of combination dosage organic fertilizer and compound fertilizer was significantly affected the observed parameters. Application of 25% organic fertilizer + 75% compound fertilizer and the use of 120 g husk charcoal/8 kg soil gave good result on growth and production of cayenne pepper. Keywords : husk charcoal, organic fertilizer and compound fertilizer